Cambios psicoemocionales de un niño de 5 años de edad que presenta trastorno espectro autista en la ciudad de Guaranda Provincia de Bolívar - Garrido Leon, Jessica Maribel (2022)
This case study deals with the change of emotions, conduct and behavior of children with Autism Spectrum Disorder; If we talk about change, we talk about processes, in which discomfort, need, motivation, awareness and our resistance to face adversity intervene, therefore we will mention the factors, causes, characteristics and consequences that have a negative impact. in the personal process of these children, so we already know that learning to treat this type of alteration corresponds to one of the elementary functions, the same ones that help regulate our behavior to feel good about ourselves and with others. In such a way that a therapeutic scheme was elaborated from the cognitive behavioral approach and it is established so that the patient, with the help of a professional, can carry it out.